THE PROTECTION OF TRADITIONAL CULTURAL EXPRESSION TO ENHANCE COMMUNITY WELFARE IN LAMPUNG PROVINCE - Ariani, Nenny Dwi (Jurnal Meta-Yuridis, 2025)
The diversity of ethnic groups in Indonesia has led to various intellectual creations by the ancestors of the nation, manifested in art, literature, and scientific knowledge, reflected in various cultural products from each ethnic group. The thoughts and creative ideas of Indonesia's ancestors are expressed in the form of cultural arts of the Lampung Indigenous Community as Traditional Cultural Expression. This study employs a socio-legal approach and a statute approach to explore the issue of protecting Traditional Cultural Expression (TCE) to enhance the welfare of the community in Lampung Province. The findings suggest that policies must focus on optimizing the role of local governments in creating regulations for the commercialization of Traditional Cultural Expression.